2017
DOI: 10.1080/09538259.2017.1348574
|View full text |Cite
|
Sign up to set email alerts
|

Financialisation and Real Investment in the European Union: Beneficial or Prejudicial Effects?

Abstract: This is the peer reviewed version of the following article: Barradas, R. (2017). Financialisation and real investment in the European Union: beneficial or prejudicial effects?. Review of Political Economy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 80 publications
2
19
0
1
Order By: Relevance
“…As a result, investors invest more in tangible and/or in financial assets, which crowds out investments in real and/or knowledge-based activities (Barradas, 2017;Barradas and Lagoa, 2017b). The sixth explanation is connected to the resources' absorption by the financial sector, which reduces the existing resources to the real and productive sectors (Cecchetti and Kharroubi, 2012;Sawyer, 2014).…”
Section: Of Financialisationmentioning
confidence: 99%
“…As a result, investors invest more in tangible and/or in financial assets, which crowds out investments in real and/or knowledge-based activities (Barradas, 2017;Barradas and Lagoa, 2017b). The sixth explanation is connected to the resources' absorption by the financial sector, which reduces the existing resources to the real and productive sectors (Cecchetti and Kharroubi, 2012;Sawyer, 2014).…”
Section: Of Financialisationmentioning
confidence: 99%
“…The motivation for the growing interest in these studies is the observed fall in investment across economies in the Global North, dubbed “investmentless growth” in recent studies that partly explained it by low asset values, increasing monopoly power and rising intangible asset shares (Döttling et al., 2017; Gutiérrez & Philippon, 2017). Early studies problematized this “slowdown of accumulation” for a range of high‐income countries and detected statistical correlations with rising financial income or payouts (Orhangazi, 2008; Stockhammer, 2004)—findings which were often confirmed by later contributions (Barradas, 2017; Barradas & Lagoa, 2017; Hecht, 2014; Tori & Onaran, 2018, 2020). At the same time, researchers tried to insert some caution by pointing out that some financial assets might actually support investment (Davis, 2018a) and that interest rates might exert greater influence over firms' decisions than financial investment in general (Clévenot et al., 2010).…”
Section: A Structured Review Of the Literaturementioning
confidence: 99%
“…Van Treeck ( 2008) aynı ülkeler ve değişkenleri ARDL yöntemini kullanarak test etmiş ve Stockhammer (2004) ile benzer sonuçları bulmuştur. Barradas (2017) finansallaşmayı finansal gelirler ve ödemeler ile ölçerek finansallaşmanın AB ülkelerinde reel yatırımlara zarar verdiğini ortaya koymuştur.…”
Section: İstikrarsızlık Görüşü: Finansal Piyasalar İstikrarsızlık Ve Krizlerunclassified